Réponses

Meilleure réponse !
2013-10-21T10:21:12+02:00
4B-13
A = 10^6  * 10-3 * 0,001 = 10^6  * 10-3 * 10^-3 = 10^0 = 1
B = 0,01 * 10^4 * 10-6 * 10^4 = 10-2 * 10^4 * 10^-6 * 10^4 = 10^(-2+4-6+4) = 10^0 = 1
4B-14
A =  \frac{65 * 10^3 * 10-5}{26 * 10^2} =  \frac{65}{26} * 10^(3-5-2) = 2,5 * 10-4 (Ecriture scientifique) = 0,00025
4B-15
C =  \frac{8 * 10^15 * 15 * 10^-6}{20 * (10^2)^5} =  \frac{8 * 15}{20} *  \frac{10^15 * 10^-6}{10^10} = 6 * 10^(15-6-10) = 6 * 10^-1 = 0,6 =  \frac{6}{10} =  \frac{3}{5}
4B-16
C =  \frac{2,1 * 10^-5}{70 * 10^-7} =  \frac{21 * 10^-6}{70 * 10^-7} =  \frac{21}{70} * 10^(-6+7) =  \frac{3}{10} * 10^1 = 3
4B-17
C =  \frac{4 * 10^6 * 3,3 * 10^-7}{6 * 10^3} =  \frac{4 * 10^6 * 33 * 10^-8}{6 * 10^3} =  \frac{4 * 33}{6}  * 10^(6-8-3) = 22 * 10^-5 = 2,2 * 10^-4 = 0,00022